Amyloidosis from the patient perspective: the French daily impact of amyloidosis study. (3rd July 2022) - Damy, Thibaud; Adams, David; Bridoux, Frank; Grateau, Gilles; Planté-Bordeneuve, Violaine; Ghiron, Yves; Farrugia, Agnès; Pelcot, Françoise; Taieb, Charles; Labeyrie, Céline; Jaccard, Arnaud; Georgin-Lavialle, Sophie
Abstract: Background: Amyloidosis is a complex group of rare conditions. For patients, amyloidosis is severely debilitating: physically and psychologically. Currently, data are lacking to evaluate the medical, economic, and social burden of systemic amyloidosis. Objective: To analyse the patient burden according to the main types of systemic amyloidosis. Methods: The French Daily Impact of Amyloidosis study was an observational, cross-sectional and non-interventional study. Adults diagnosed with light chain (AL), transthyretin (ATTR), amyloid A (AA) and other rare forms of amyloidosis were eligible. Data regarding amyloidosis prevalence, diagnosis, management, and impact on everyday life were collected using a study-specific survey built by the Association Française Contre l'Amylose (AFCA) and the four French National Referral Centres for Amyloidosis. Results: A total of 603 patients, predominantly male (65%) with an average age of 66.8 years, including 170 AL, 224 ATTRv, 109 ATTRwt and 25 AA amyloidosis patients, completed the study-specific survey. The median delay from presentation to confirmed diagnosis was 27.4 months but varied according to amyloidosis type. Patients before diagnosis had breathlessness (49%), tingling sensation (33%), pain (28%), difficulty in walking (28%) and weight loss (22%). Amyloidosis was most frequently suspected (49%) and confirmed (57%) in local hospitals but managed in French amyloidosis referral centres (58%). Patients often reported problems with mobility, usual activities, pain/discomfort and anxiety/depression, but not with self-care. Conclusions: Systemic amyloidosis severely impacts daily life. The delay to confirmed amyloidosis diagnosis needs to be reduced. Early, effective treatment is required to optimise patient benefits.